2021
DOI: 10.1186/s12864-021-08166-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated omics analysis reveals sirtuin signaling is central to hepatic response to a high fructose diet

Abstract: Background Dietary high fructose (HFr) is a known metabolic disruptor contributing to development of obesity and diabetes in Western societies. Initial molecular changes from exposure to HFr on liver metabolism may be essential to understand the perturbations leading to insulin resistance and abnormalities in lipid and carbohydrate metabolism. We studied vervet monkeys (Clorocebus aethiops sabaeus) fed a HFr (n=5) or chow diet (n=5) for 6 weeks, and obtained clinical measures of liver function,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 111 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In addition, previous studies used only RNA-Seq data to quantify molecular changes; whereas, this study integrated transcriptomic, proteomic, and metabolomic data. In previous studies, we (Cox et al, 2021) and others (e.g., (Meng et al, 2019) have demonstrated greater power to detect phenotypically relevant molecular pathways using integrated omics compared to transcriptomics analyses alone.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, previous studies used only RNA-Seq data to quantify molecular changes; whereas, this study integrated transcriptomic, proteomic, and metabolomic data. In previous studies, we (Cox et al, 2021) and others (e.g., (Meng et al, 2019) have demonstrated greater power to detect phenotypically relevant molecular pathways using integrated omics compared to transcriptomics analyses alone.…”
Section: Introductionmentioning
confidence: 84%
“…Despite the remarkable activity of CD19-directed chimeric antigen receptor T cell (CART19) therapy in treating B-cell hematologic malignancies, 1 , 2 limitations include 1) the development of potential life-threatening complications such as neurotoxicity (NT) and cytokine release syndrome (CRS) 3 , 4 and 2) lack of durable response. 5 8 Emerging literature suggests that inhibitory myeloid cells and their cytokines play an important role in inducing CART cell toxicities and contribute to CART inhibition. 9 12 Specifically, and of relevance to the work presented in this manuscript, granulocyte-macrophage colony-stimulating factor (GM-CSF) is implicated in the development of NT and CRS after CART19 therapy based on correlative studies from pivotal clinical trials.…”
Section: Introductionmentioning
confidence: 99%